Videocapillaroscopic findings in the microcirculation of the psoriatic plaque during etanercept therapy. (13th June 2013) - Stinco, G.; Buligan, C.; Maione, V.; Valent, F.; Patrone, P.
Summary: Background: Vascular endothelial growth factor (VEGF) is a pivotal cytokine in the pathogenesis of psoriasis, and upregulation of VEGF by tumour necrosis factor (TNF)‐α and inflammatory factors causes marked alterations in the cutaneous microcirculation. Etanercept is a fully soluble TNF receptor fusion protein that primarily binds soluble TNF‐α, thus blocking its pro‐angiogenic function. Aim: To assess the modifications in the superficial capillary bed in psoriatic plaques during treatment with etanercept. Methods: The study enrolled 22 patients (13 men, 9 women; age range 31–74 years) with plaque psoriasis resistant to conventional therapy. The patients were stated on etanercept 50 mg/week, which was continued for 24 weeks. At the beginning of the study (baseline), and at weeks 6, 12, 18 and 24, in vivo videocapillaroscopy analysis of a selected plaque was performed. Levels of erythema, scaling and infiltration were assessed using a four‐point plaque severity score, with an overall score obtained by the sum of these three scores. The Psoriasis Activity and Severity Index (PASI) was also determined. Results: Etanercept produced a significant reduction in PASI, plaque severity score and diameter of the basket‐weave area at every time point. Four patients had complete remission, although none of the patients regained a normal capillaroscopic pattern. Conclusions: Similar to other conventional therapies, etanercept is able to improve PASI, plaque severity score and basket‐weave area diameter, but it is unable to induce normalization of the microcirculation in psoriatic plaques.